Model of the commodity market with information about price trends: limiting cases - Kalitine, Boris S.; Novikova, Natalia V. (Journal of the Belarusian State University. Economics, 2022)
A discrete market model with given supply and demand functions is considered, provided that the behaviour of producers and consumers can be based on information about the tendency of prices of goods or services. The conditions concerning the parameters of the model, under which an economic equilibrium exists and is unique, are derived.